Signing on the dotted line: the lived experience of book contracts in contemporary Australian small-press publishing. - Masson, Sophie (New Writing: The International Journal for the Practice & Theory of Creative Writing, 2020)
The publishing contract is the central legal feature of any publishing professional's life, whether creator, literary agent, or publisher. And with small press becoming an ever more important part of the Australian publishing scene, the contracts landscape has diversified and become more complex. There's a wealth of information on what you should and shouldn't do, and what the perfect contract looks like. But what's it like in reality, beyond the clause and sub-clause? For though it's an important legal document, the contract also represents an intense lived experience for all those who are a party to it, especially in the small-press sector. This article, based on interviews with a range of creators (authors and illustrators), literary agents, small-press publishers and industry body representatives, presents an illuminating snapshot of the contemporary contract experience in the Australian small-press sector. Not intended as a formal analysis of the contracts landscape but rather as an intimate insight into the individual lived experience of contemporary Australian contracts, whether that be for creators or publishers, the article addresses questions covering the contemporary challenges and opportunities of 'signing on the dotted line'.